2020
DOI: 10.3390/ijerph17062003
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cesarean Birth with Body Mass Index Trajectories in Adolescence

Abstract: Background: This study aimed to identify patterns of body mass index (BMI) changes in adolescence and to assess whether delivery mode (Cesarean and vaginal delivery) was associated with BMI trajectories. Methods: This study was conducted among 569 adolescents aged 10-15 years that resided in the city of Zibo, China. The height and weight of each participant were repeatedly measured at 10, 11, 12, 13, 14 and 15 years. Group based trajectory modeling (GBTM) was used to estimate BMI change trajectories, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…A large amount of evidence supports that obesity during birth and infancy has a great influence on obesity in later life stage, including preschool-age and adolescence (44). Zhou's study had focused on the dynamic changes in children's growth and development and confirmed that CS significantly increased the risk of "progressive obesity" trajectory (OR = 2.50, 95% CI: 1.42, 4.41) at the ages of 10-15 years (45). Due to the limited data, we could not provide powerful findings on the effect of ECS on the occurrence of obesity in adolescents in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…A large amount of evidence supports that obesity during birth and infancy has a great influence on obesity in later life stage, including preschool-age and adolescence (44). Zhou's study had focused on the dynamic changes in children's growth and development and confirmed that CS significantly increased the risk of "progressive obesity" trajectory (OR = 2.50, 95% CI: 1.42, 4.41) at the ages of 10-15 years (45). Due to the limited data, we could not provide powerful findings on the effect of ECS on the occurrence of obesity in adolescents in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…Most studies on the association between cesarean delivery and obesity have been done including children 4,5,6,17,32,33,34,35,36,37,38 and adults 5,16,39,40,41 . Some studies have been carried out including adolescent individuals 4,5,6,17,42 , but there are few studies conducted with individuals in their late adolescence 4,5,27,29 . This study was carried out with people in this age group because they have already gone through the growth stage and are no longer under the hormonal effects of adolescence, which provide greater deposition of adipose tissue 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the differences in body fat percentage between East Asians and Europeans, the definition of overweight or obesity was based on the Chinese standard "Screening for overweight and obesity among school-age children and adolescents", standard number WS/T 586–2018 [ 35 , 36 ]. The process for identifying overweight or obesity in school-aged children and adolescents between the ages of 6 and 18 was described in the standard, together with the technical prerequisites for this procedure.…”
Section: Methodsmentioning
confidence: 99%